Reason and Revelation in Islamic Education: A Comparative Study of Al-Ghazali’s and Ibn Rushd’s Educational Thought in the Contemporary Context - Zainudin, Agus; Hudi, Saman; Suriyani, Aysha Imeylian; Yakoh, Mahnawawe (JURNAL AT-TURAS, 2026)
Islamic education today often experiences an imbalance between spiritual-moral formation and rational-intellectual development. This indicates a theoretical gap in developing an integrated educational framework in Islamic thought. Although Al-Ghazali and Ibn Rushd represent two main paradigms in this debate, their educational ideas are rarely studied comparatively to address this issue. This study aims to comparatively analyze the educational thoughts of Al-Ghazali and Ibn Rushd and to explore their relevance to contemporary Islamic education. This research uses qualitative library research by examining primary and secondary literature related to these two scholars. This study finds that Al-Ghazali emphasizes education as spiritual purification and moral perfection based on divine guidance, while Ibn Rushd emphasizes intellectual development through reasoning and empirical inquiry. Rather than being contradictory, their perspectives complement each other. Integrating ethical-spiritual and rational-intellectual approaches offers a holistic framework for contemporary Islamic education.